Field experience in the research process: Contributions to breaking the reason/emotion dualism - Herrera-Farfan, Nicole (2022)
This article aims to highlight the epistemic value of emotions in research, considering feminist criticism of the hierarchical power relationship that is traditionally maintained between the subject and the researcher in qualitative methodology. Through field experience and elements that situate and empower the subjects, emotionally sensed knowledge is generated and validated by those who experience it. The co-production of narrative life stories becomes a central element in the proposed analysis, providing an opportunity to comprehend the dynamics of male dominance and the exercises of power prevalent in the intimate relationships of women who have experienced violence from incarcerated men, as presented in the experience of La Chora. The methodological and creative approach, therefore, becomes crucial in the theoretical and methodological discussion.